Viajando à margem da história: os sentidos do tempo em Caim, de José Saramago - Machado, Janer Cristina (2013)
Myth and history are instances that intertwine strongly in Caim (2009), by Portuguese novelist José Saramago, whose incisive reading of the biblical text is made in the light of a conception of free traffic by time and introducing questions about the meaning of life, the men s place in legend and his role in chronicle. Starting from this fact, this study seeks to elucidate the representations of temporalities in Saramago s last work, mainly using the concepts developed over time by Paul Ricoeur and notions of chronotope proposed by Mikhail Bakhtin, emphasizing the approaches of historical time and mythical time in search of sense of time to the experiences of the protagonist. Investigating the concepts over time and their dynamics as a leitmotiv of the protagonist's relationship with the deity and the world, is outlined an ouroboros that weaves Myth and History, leading the protagonist in an intense journey of challenges and revelations that refers to the defense of former cultural constructs, simultaneously open new meanings to human existence.